Oriented growth of nanocrystalline gamma ferric oxide in electrophoretically deposited films - Bhave, T. M.; Balasubramanian, C.; Nagar, H.; Kulkarni, S.; Pasricha, R.; Bakare, P. P.; Date, Sadgopal K.; Bhoraskar, S. V. (Hyperfine Interactions, 2005)
Films of nanocrystalline gamma-Fe2O3 were deposited on silicon substrates by using the technique of electrophoretic deposition. The precursor powder was nanocrystalline gamma-Fe2O3, which was synthesized, using DC arc plasma in the oxygen ambient by vapour-vapour interaction in gas phase condensation; at a stabilized arc current of 40 A. This powder was characterized by X-ray diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and Mossbauer Spectroscopy. An increase in directional coercivity was observed in case of films deposited on silicon substrates, which is dramatically significant. Preferred orientation of almost similar sized nanocrystalline magnetic domains in deposited films is evident from the results of X-ray diffraction and Transmission Electron Microscopy results. The preferred alignment of the nanocrystallites seems to be responsible for the significant changes observed in magnetic properties of films.